ANALISIS KESALAHAN PENGGUNAAN EJAAN BAHASA INDONESIA DALAM BERITA UNGGAHAN AKUN RESMI FACEBOOK PONDOK PESANTREN DARUSSALAM BLOKAGUNG BULAN OKTOBER SAMPAI DESEMBER 2021 - Silma Humairo (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This research was conducted to describe the form of Indonesian spelling errors in the news uploaded to Pondok Pesantren Darussalam's facebook page and to find out the form of correcting Indonesian spelling errors in the news uploaded to Pondok Pesantren Darussalam's facebook page. The method used in this research is descriptive qualitative. The techniques used for research are tapping techniques, speaking techniques free of involvement, and note-taking techniques. Research that is included in this syntactic level, more specifically related to spelling errors, the researcher describes errors in the use of letters, punctuation errors, word writing errors, and absorption word writing errors found in news uploaded to Pondok Pesanren Darussalam Blokagung's Facebook Facebook. The results and conclusions of this study are that there are 297 forms of errors consisting of (a) 184 errors in the use of letters, (b) 81 errors in writing words, (c) 13 errors in the use of punctuation marks, (d) writing errors absorption words as many as 19 errors. Therefore, the highest number of errors occurs in the use of letters.